2009
DOI: 10.1371/journal.pone.0007419
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin — A Novel Marker of Obesity

Abstract: BackgroundThe two inflammatory molecules, S100A8 and S100A9, form a heterodimer, calprotectin. Plasma calprotectin levels are elevated in various inflammatory disorders. We hypothesized that plasma calprotectin levels would be increased in subjects with low-grade systemic inflammation i.e. either obese subjects or subjects with type 2 diabetes.Methodology/Principal FindingsPlasma calprotectin and skeletal muscle S100A8 mRNA levels were measured in a cohort consisting of 199 subjects divided into four groups de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
72
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 10 publications
13
72
1
4
Order By: Relevance
“…In agreement with previous results (3,29), we showed an increase of calprotectin concentrations in both obesity and obesity-associated T2D. These data together with the strong positive association with anthropometric variables such as BMI, BF, waist circumference and WHR highlight the link between calprotectin and obesity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous results (3,29), we showed an increase of calprotectin concentrations in both obesity and obesity-associated T2D. These data together with the strong positive association with anthropometric variables such as BMI, BF, waist circumference and WHR highlight the link between calprotectin and obesity.…”
Section: Discussionsupporting
confidence: 92%
“…However, the lack of correlation between gene expression levels and the circulating concentrations of calprotectin suggests that in addition to VAT, a further source is contributing to the increased plasma calprotectin levels in obesity-associated T2D. In this sense, no evidence of dysregulation of mRNA levels of S100A8 in obese or T2D patients in skeletal muscle as well as no correlation with circulating calprotectin levels have been described (3). To gain more insight into the source of production, we further analyzed the gene expression levels of S100A8/A9 in isolated adipocytes and SVFCs, finding a higher expression in the SVFCs.…”
Section: O V E M B E R -D E C E M B E R 2 0 1 1 C a L P R O T E C T Imentioning
confidence: 99%
“…Recently, increased circulating calprotectin concentration has been found in obese subjects (17,18). Nijhuis et al (18) evaluated the activation state of neutrophils in nine lean and 37 morbidly obese subjects and after bariatric surgery-induced weight loss in nine obese subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating calprotectin concentration (as a marker for neutrophil activation) was significantly increased in morbidly obese subjects and decreased after weight loss (18). Mortensen et al (17) reported that circulating calprotectin concentration was associated with BMI in individuals without type 2 diabetes (T2D; 62 nonobese and 41 obese subjects aged between 50 and 60 years old). They found no significant association between circulating calprotectin and parameters of glucose homeostasis (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation